Uncovering the role of superplasticizer in developing nano-engineered ultra-high-performance concrete - Wang, Lili; Ma, Yitong; Li, Liangwei (Frontiers in Materials, 2023)
The effect of superplasticizer (SP) on the performance of ultra-high-performance concrete (UHPC) and ultra-high-performance fiber-reinforced concrete (UHPFRC) has been systematically investigated aiming to optimize the use of SP. The slump flow, and V-funnel time were employed to evaluate the impact of SP on the workability, while compressive strength had been used for mechanical property. Moreover, the packing density, as well as the water film thickness had been calculated to uncover the mechanism. The obtained results indicated that the addition of SP improved the workability of specimens with an ultimate-low water-to-binder (W/B) ratio, while it benefited the strength development of UHPC with a lower W/B ratio. This novel phenomenon (SP enhances the mechanical properties of UHPC) is due to the fact that SP reduced the water film thickness and enhanced the packing structure, therefore resulting in an increased compressive strength. For UHPFRC, similar trends can be witnessed regarding the flowability. However, the alternation of the fresh behavior of UHPFRC, attributed to the inclusion of SP, had an obvious impact on the fiber distribution, which altered the strength development of UHPFRC. This study revealed the significant effect of SP on the performance, especially on the strength development, of UHPC and UHPFRC.